UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN JELANTIR (Conyza sumatrensis (Retz.) E. Walker) DALAM SEDIAAN DEODORAN SPRAY TERHADAP BAKTERI Staphylococcus epidermidis - Agis Destriawan; Reni Mulyani; Salih Muharam (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The bacteria Staphylococcus epidermidis is known to cause body odour in the human body. A common method to kill bacteria that cause body odour is deodorant. Commercial deodorants contain aluminium chlorohydrate and the compound is known to increase the risk of skin cancer and alzheimer's disease. A candidate for a safer deodorant is one made from natural ingredients. One of the natural ingredients that has potential as a deodorant is jelantir leaves. The purpose of this study was to extract and characterise phytochemical compounds and test their antibacterial activity in deodorant spray preparations on Staphylococcus epidermidis. The extraction method used was maceration using ethanol solvent, extract characterisation using UV-Vis spectrophotometry and antibacterial test of deodorant spray preparation of jelantir leaf extract using disc diffusion. The results showed that jelantir leaf extract contained flavonoids 5.5727 ±0.1336 (%w/w QE), saponins 8.6472 ±0.0353 (% w/w SE), tannins 2.1448 ±0.0506 (%w/w TAE), steroids 1.0231 ±0.0083 (%w/w BSE), triterpenoids 0.9090 ±0.0030 (%w/w UAE) and the antibacterial test results had the highest inhibition zone diameter of 13.50 ±0.50 (mm) in formula 30 (%w/v).